The x values are the same for both green dots, so you are looking at a simplified version of the distance formula.
d = sqrt( (x2 - x1)^2 + (y2 - y1)^2 )
Since x1 = x2 = 5, the first set of brackets = (5 - 5) = 0
d = sqrt( y2 - y1)^2 )
d = y2 - y1
y2 = 5
y1 = - 1
d = 5 - - 1
d = 6 Answer
Answer:
When simplified this equation equals 8.
Step-by-step explanation:
Let me show you my work.
4 ( 3.5 - 1.5 ) = 4 ( 2 )
4 ( 2 ) = 8 because 4 times 2 = 8
Hope this helps. . .
UwU
Answer:
16
Step-by-step explanation:
Lets solve this step by step,
First we insert 8 in x's place:
(8 - 4) + 12
Now we solve:
8 - 4 = 4
(4) + 12
4 + 12 = 16
Answer: 16
Hope this Helps
Answer:
w=17
Step-by-step explanation:
-243=-9(10+w)
-243=-90-9w
+90 +90
-153=-9w
17=w
hope this helps :)
<span>Simplifying
2x + 18y = 36
Solving
2x + 18y = 36
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-18y' to each side of the equation.
2x + 18y + -18y = 36 + -18y
Combine like terms: 18y + -18y = 0
2x + 0 = 36 + -18y
2x = 36 + -18y
Divide each side by '2'.
x = 18 + -9y
Simplifying
x = 18 + -9y</span>